Pengaruh Pemutihan Pajak Kendaraan Bermotor terhadap Penerimaan Pajak Pajak Kendaraan Bermotor Di Provinsi Jawa Barat Periode 2019-2020 - Fachrel Ichlas; Lili Indrawati; Yanti Rufaedah (Indonesian Accounting Research Journal, 2022)
This a study was conducted to measure how much influence there is in the implementation of the motor vehicle tax whitening program on motor vehicle tax receipts at the Regional Revenue Agency of West Java Province in 2019-2020. The analysis method uses classical assumption test, simple regression analysis, and hypothesis testing. Analysis of the processed data using the SPSS version 25.0 application. This study results that the abolition of motor vehicle tax has a significant effect on motor vehicle tax revenues. The magnitude of the effect of whitening motor vehicle taxes on motor vehicle tax revenues is 90%, while the remaining 10%’is influenced by other variables or factors not examined in this study.